Nós não vamos sucumbir : o acontecimento noventa anos de Elza Soares - Barbara Cristina Lima (2021)
The objective of this research is to investigate how the ninety-year anniversary of singer Elza Soares reveal moments in her trajectory that show us her construction as a celebrity, as well as the values of Brazilian society. Therefore, we use the concepts of celebrity, intersectionality and event to support our theoretical discussion. We took as our corpus a segment from the TV program “Domingo Espetacular”, an episode of the podcast “G1 Ouviu”, an interview from the program “Metrópolis” and the 2020 carnival parade of Mocidade Independente de Padre Miguel. Another central element is Elza's vast musical repertoire, which helped us to structure the discussions and recount the singer's story from the milestone of her nineties. From this material, we build our methodological design. First, a content analysis allowed us to identify and organize our empiricism in four dominant thematic axes (Work, Time, Faith and Voice). We then use the analytical possibilities offered by the concept of event. The findings of our research reveal that Elza has been wronged and oppressed on many levels, but that she has found, like so many other Brazilians, a way to keep going back on top.